Letter to the editor: Critical assessments of the current state of scientific knowledge, terminology, and research needs concerning the ecological effects of elevated atmospheric nitrogen deposition in China - Pan, Yuepeng; Liu, Yongwen; Wentworth, Gregory R.; Zhang, Lin; Zhao, Yuanhong; Li, Yi; Liu, Xuejun; Du, Enzai; Fang, Yunting; Xiao, Hongwei; Ma, Hongyuan; Wang, Yuesi (Atmospheric environment (1994), 2017)
In a publication in Atmospheric Environment (http://dx.doi.org/10.1016/j.atmosenv.2015.10.081), Gu et al. (2015) estimated that “the total nitrogen (N) deposition in 2010 was 2.32 g N m−2 yr−1” in China. This value is comparable with previous estimations based on a synthesized dataset of wet/bulk inorganic N deposition observations, which underestimates the total N deposition since their algorithm (equations (2) and (3) in their paper) does not account for dry deposition of NH3, HNO3, NOx and wet/dry deposition of HONO and organic nitrogen (e.g. amines, amides, PAN). Indeed, Gu et al. (2015) mixed the terminology of wet/bulk deposition and total deposition. Another flawed assumption by Gu et al. (2015) is that all inorganic N in precipitation estimated by their algorithm originates from fertilizer and coal combustion. This is incorrect and almost certainly causes biases in the spatial and temporal distribution of estimated wet/bulk inorganic N deposition (Fig. 5 in their paper), further considering the fact that they neglected important N sources like livestock and they did not consider the nonlinearity between various sources and deposition. Besides the input data on N deposition, the model validation (Sect. 2.3.2) described in their paper also requires clarification because the detailed validation information about the time series of observational dataset versus modeling results was not given. As a result of these combined uncertainties in their estimation of N deposition and the lack of detail for model-measurement comparison, their estimates of the impacts of N deposition on carbon storage in Chinese forests may need further improvement. We suggest the clarification of the terminology regarding N deposition, especially for wet deposition, bulk deposition, gaseous and particulate dry deposition or total deposition since the accurate distinction between these terms is crucial to investigating and estimating the effects of N deposition on ecosystems.